The impact of amortization of gene therapies funding on the results and conclusions of CEMs and BIMs - Hubert Polek; Justyna Janik; Ewelina Paterak; Monique Dabbous; Michał Pochopień; Mondher Toumi (Journal of Market Access & Health Policy)
ABSTRACTBackground: Gene replacement therapy (GRT) is a treatment method used to combat or prevent various diseases. Its high one-off cost constitutes a major obstacle for successful market access. This paper aims to assess and discuss the applicability of amortization in models, such as cost-effectiveness models (CEMs) and budget impact models (BIMs) informing HTA recommendations and reimbursement decisions.Methods and findings: A hypothetical CEA and BIA were considered. The objective was to compare the GRT with and without amortization. A straight-line amortization model was used. The CEM and BIM were considered and assessed based on two set of scenarios: considering different amortization duration or different discounting rate. The impact of amortization against the total cost of gene therapy was assessed for all the scenarios.The cost difference between GRT with and without amortization in relation to its total cost was -$58,855, thus amortization does not have a significant impact on the results and conclusions of the cost-effectiveness analysis. For BIM in the base case, amortization had no impact on the results.Conclusion: Amortization has negligible impact on the results of CEM and total BIM and no impact on the conclusions from the model. One exception is the budget impact in case of an amortization period longer than the time horizon of BIM, where a half of the GRT price is moved beyond the model time horizon. Amortization has a distinguishing effect from an accounting perspective, but it does not have any implication for payers.